Analisis Forensik Digital E-Commerce pada Website Rental Mobil Menggunakan Metode NIST - Yusuf Fadhilah; Gregorius Hendita Artha Kusuma (Prosiding SISFOTEK, 2019)
As information technology develops, content and content develop more than information technology for example e-commerce. Increasingly requires maturity to address the name of the development of information technology. The development of e-commerce is also used by merchant sellers and services to make online transactions to consumers, for example through a website that provides car rental services through the website www.jetstarrental.com. In this case it is undeniable that there are individuals who commit fraud by providing rental services on the website www.jetstarrental.com and take advantage of situations such as this to get personal benefits through fake fraud or commonly called online transaction fraud that the seller of the rental service does to the next consumer called cybercrime. To solve this case, it requires computer forensic science to obtain digital evidence, which can then be brought to the realm of law to solve it.